A alfabetização e o letramento na compreensão e nas práticas dos professores alfabetizadores de uma escola no município de Barcarena-PA - BRABO, Elizyane Valente (2022)
For many years literacy was reduced to simply obtaining a code based on the correspondence between phonemes and graphemes. However, the main criticisms are due to the fact that through this traditional teaching model, subjects who read and write mechanically have been formed. In this scenario, it is necessary to recognize new practices aimed at overcoming traditionalism, thus emerging literacy, which carries in its context the sociocultural dimension of written language. It is up to the teacher to use social practices to mediate them in the school space, so, as they become literate, the child will become aware of the world around them. Therefore, recognizing its importance to make the literacy process viable, the problem arises: how is literacy reflected in the pedagogical practice of literacy teachers? The main objective of this study is to identify how literacy teachers link literate culture to their practices, and for that, the research consisted of a qualitative approach. Data collection was carried out in a school in the city of Barcarena and included observation in 1st and 2nd grade classes of elementary school and interviews with the teachers of the classes. The results obtained in the interview clipping lead us to think that there are still gaps in understanding about the concepts of literacy and literacy, which, in a way, ends up making it difficult to insert literate culture into teaching practice. Therefore, this research sought to contribute to the academic community to expand the understanding of these two processes, as well as their relevance to the social environment.